The efficacy of different doses of Midazolam added to Lidocaine for upper extremity Bier block on the sensory and motor block characteristics and postoperative pain - Azim Honarmand; Mohammadreza Safavi; Koorosh Nemati; Padideh Oghab (Wolters Kluwer Medknow Publications, 2015)
Objective: This study was designed to evaluate the effect of different doses of midazolam on anesthesia and analgesia quality when added to lidocaine during the intravenous regional anesthesia (IVRA). Methods: One hundred and forty patients underwent hand surgery were randomly allocated into four groups to receive 3 mg/kg lidocaine 2% diluted with saline to a total volume of 40 mL in the control Group L-C (n = 35), 30 μg/kg midazolam plus 3 mg/kg lidocaine 2% diluted with saline to a total volume of 40 mL in the midazolam Group L-M1 (n = 35), 40 μg/kg midazolam plus 3 mg/kg 2% lidocaine diluted with saline to a total volume of 40 mL in the midazolam Group L-M2 (n = 35), and 50 μg/kg midazolam plus 3 mg/kg lidocaine 2% diluted with saline to a total volume of 40 mL in the midazolam Group L-M3 (n = 35). Sensory and motor block and recovery times, tourniquet pain, intra-operative analgesic requirement, and visual analog scale (VAS) scores were recorded. Findings: Onset time of sensory and motor block in L-M3 Group was shorter than the L-M2 and L-M1 and L-C Groups (P < 0.001). Furthermore, prolonged sensory (P = 0.005) and motor recovery time (P = 0.001) in L-M3 were longer than the other groups. Intra-operative VAS score and intra-operative fentanyl consumption in L-M3 were lower than the other groups (P < 0.001). The numbers of patients needed to pethidine in Group L-M3 were significantly less compared with the other groups (P = 0.035). VAS scores were significantly lower in Group L-M3 in different time intervals in the postoperative period compared with the other groups (P < 0.001). Conclusion: Addition of 50 μg/kg midazolam for IVRA (Group L-M3) enhanced intra-operative analgesia and improved anesthesia quality better than other groups receiving lower midazolam doses as well as a control group.